Maxillary Growth Evaluation After Cleft Palate Repair Using Goslon Criteria: Preliminary Study - Simamora, Huntal; Lamtiur, Evie; A., Nur; Handayani, Siti; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: The goal of palatoplasty is to achieve normal maxillofacial growth, normal speech, and prevent hearing loss. Disturbance of maxillary growth may occur in cleft lip palate patients after palatoplasty. To determine how many patients later developed a disrupted maxillary growth following operations, a retrospective study was designed to evaluate patients with complete unilateral cleft lip and palate who have undergone two-flap palatoplasty.Methods:A retrospective analytic study evaluated the maxillary growth of 15 consecutive unilateral cleft lip and palate patient aged around 8-year-old treated in the Division of Plastic Surgery Cipto Mangunkusumo Hospital, Jakarta. Cephalogram and dental study models were used to assess growth. Cleft lip and palate repair were performed to all patients without alveolar bone graft or any orthodontic treatment. Result: The cephalogram shows that 53,3% of the patients developed maxillary hypoplasia post palatoplasty. Mean value of the Goslon Yardstick was 3,53 (intermediate category by Goslon criteria).No patient fell into the Goslon 1 or 5 categories. Discussion: Disturbed maxillary growth is postulated to be caused by the manipulation and suturing of the maxillary vomer, and scarring of the dentoalveoli post-surgery. Another contributing factor is the intrinsic tissue deficiency. Conclusion: Maxillary hypoplasia is a possible complication following two !ap palatopasty, affecting either anteroposterior, transversal and vertical maxillary growth. This finding needs to be proven especially after the process of growth ceased. It is highly probable that maxillary disruption is higher when the two flap palatoplasty technique leaves lateral areas of denuded bone on the maxillary tuberosity.